Curation of the John and Phil Palmquist Archaeological Collection: Implementing SAA "Responsible and Responsive Stewards" Best Practices. Issue 1 (February 2022) - Doershuk, John F.; Davis, Warren D.; Palmquist, John
Abstract: The 2018 SAA statement encouraging collaboration between archaeologists and "responsible and responsive stewards" included recommendations epitomizing decades of established practice at the University of Iowa Office of the State Archaeologist (OSA), a research center housing the State Archaeological Repository of Iowa. At the time the SAA statement was published, OSA staff were actively implementing a grant supporting transfer to the State Repository of the John and Phil Palmquist Archaeological Collection. This grant was designed to provide hands-on research experience for undergraduate students interested in archaeology and collections management while recording improved site locational data and artifact specific documentation, including on relatively rare (for the area) red pipestone artifacts. Although modest by some standards, the Palmquist Collection includes 860 artifacts from 26 locations recorded through 40 years of surface survey by the family in a portion of Iowa that is rarely the focus of professional archaeologists. This article provides a case study of responsible archaeological practice implementing SAA recommendations, including treating collector-collaborators with respect, encouraging collector assistance in the recording of finds, capturing research data from a private collection, and facilitating curation of privately owned materials. We include brief consideration of the impact of the Palmquist Collection on the understanding of southwestern Iowa archaeology.